Haunted houses and family ghosts of Kentucky - Montell, William Lynwood, 1931- (University Press of Kentucky, 2001)
"An all-new collection of amazing ghost stories from the author of the bestselling Ghosts across Kentucky . Kentucky has a rich legacy of ghostly visitations. Lynwood Montell has harvested dozens of tales of haunted houses and family ghosts from all over the Bluegrass state. Many of the stories were collected from elders by young people and are recounted exactly as they were gathered. Haunted Houses and Family Ghosts of Kentucky includes chilling tales such as that of the Tan Man of Pike County, who trudges invisibly through a house accompanied by the smell of roses, and the famed Gray Lady o